PENGARUH KONSENTRASI DAN FREKUENSI APLIKASI EFFECTIVE MICROORGANISMS-4 (EM-4) TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SAWI (Brassica juncea L.) - Kurniawati ardi,Bahrudin,Ramal Yusuf, Dwi (AGROTEKBIS, 2016)
This research aimed to determine the effect of Effective Microorganisms-4 (EM-4) concentrations and its application frequency and their interactions on growth and yield of green mustard plant. The experiment was conducted from November 2014 until January 2015 at Mantikulore Sub District, Palu, at an altitude about Â± 50 m above sea level. This research was carried out using a Randomized Block Design (RBD) with two factors and three replications. The first factor was the concentration of EM-4 (A) with 3 (three) levels : K1 (0,5 %), K2 (1,0 %) and K3 (1,5 %), and the second factor was the application frequency of EM-4 also with 3 (three) levels : A1 (1 time; 1 week after planting-WAP), A2 (3 times; 1, 3, and 5 WAP) and A3 (5 times; 1, 2, 3, 4 and 5 WAP). The experimental data were analyzed using analysis of variance method followed by HSD (Honestly Significant Difference) Test at 5%. The results of the research showed that the application of various concentrations of EM-4 had a significant effect on plant height (cm) at age 4, 5, and 6 WAP, number of leaves at age 5 WAP, root fresh weight (g, and gave a very significant effect to root dry weight (g). The application frequency of EM-4 gave an effect to plant height at age 5 WAP, number of leaves at age 5 and 6 WAP, and root length (cm). Whereas the interaction between both factors only had a significant effect on number of leaves at the age of 5 WAP.